(untitled) (MMIT Proceedings, 2025)
This article explores the ethical and educational implications of Karl Popper’s philosophy, focusing on his ideas of critical rationalism and the open society. It argues that Popper’s emphasis on the provisional nature of knowledge carries moral responsibilities — openness, intellectual humility, and a readiness for continuous self-correction. Education, in this context, is viewed as the process of developing critical thinking, fostering ethical awareness, and preparing individuals to participate in an open and democratic society. The article highlights the importance of accepting errors as opportunities for learning and moral growth, emphasizing that Popper’s insights remain profoundly relevant to contemporary educational theory and practice in an era of information overload and rapid social change